Power to the people - Ingraham, Laura; ebrary, Inc. (Washington, DC : Regnery Pub., 2007)
Radio personality Laura Ingraham is fed up with the rule of the élites, and issues a call to arms--a plea to reinvigorate our birthright of liberty, to reconnect to our American heritage, to revive our commitment to traditional, conservative principles, and to grow as people by summoning our moral resolve and living our faith. Amidst these rallying cries, Ingraham reveals her battle with cancer and the surprising gifts the insidious illness bestowed upon her. She challenges people to not only take back the power, but to also give of themselves to recapture America's spirit and greatness.--From publisher description.
Power to the family -- Don't fence me in-- but please fence them out! -- Protecting the people -- Judging the judges -- Keeping it local -- Saving our pornified culture -- School's out-- of control -- The revenge of the "loud folks" -- Blinding us with science -- Taking the real power trip.
Includes bibliographical references (p. 323-347) and index.
Electronic reproduction.
Keywords: Social problems -- United States; Social values -- United States; Elite (Social sciences) -- United States; Liberalism -- United States; Conservatism -- United States; United States -- Social conditions -- 1980-; United States -- Politics and government -- 2001-2009.; United States -- Moral conditions; Electronic books